2023
DOI: 10.1002/anie.202307641
|View full text |Cite
|
Sign up to set email alerts
|

Fluorogenic and Cell‐Permeable Rhodamine Dyes for High‐Contrast Live‐Cell Protein Labeling in Bioimaging and Biosensing

Abstract: The advancement of fluorescence microscopy techniques has opened up new opportunities for visualizing proteins and unraveling their functions in living biological systems. Small‐molecule organic dyes, which possess exceptional photophysical properties, small size, and high photostability, serve as powerful fluorescent reporters in protein imaging. However, achieving high‐contrast live‐cell labeling of target proteins with conventional organic dyes remains a considerable challenge in bioimaging and biosensing d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 67 publications
(130 reference statements)
0
6
0
Order By: Relevance
“…Recently, the Johnsson group reported that the transformation of the carboxylic acid into amide can effectively regulate the equilibrium of rhodamine dyes, shifting them towards the non‐fluorescent spirolactone form [18] . While this modification endows probes with high signal‐to‐noise ratio in protein labeling, [18c] it poses challenges in constructing activated probes due to the lack of suitable modification sites. Adapting this strategy to long‐wavelength rhodol derivates might offer a viable solution to resolve the current problems, and create long‐wavelength fluorophores that can be used to construct fluorescent probes with ultrahigh sensitivity.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, the Johnsson group reported that the transformation of the carboxylic acid into amide can effectively regulate the equilibrium of rhodamine dyes, shifting them towards the non‐fluorescent spirolactone form [18] . While this modification endows probes with high signal‐to‐noise ratio in protein labeling, [18c] it poses challenges in constructing activated probes due to the lack of suitable modification sites. Adapting this strategy to long‐wavelength rhodol derivates might offer a viable solution to resolve the current problems, and create long‐wavelength fluorophores that can be used to construct fluorescent probes with ultrahigh sensitivity.…”
Section: Resultsmentioning
confidence: 99%
“…Owing to their high fluorescence quantum yield, good photostability, biocompatibility and high molar extinction coefficient, 1,2 xanthene fluorophores such as fluorescein and rhodamine are widely used in biological detection and fluorescence imaging. 3,4 However, the fluorescence emission wavelength of conventional xanthene fluorophores is mainly in the visible light range of 500-650 nm, which cannot meet the needs of more extensive research. In contrast, near-infrared (NIR) fluorophores have the advantages of low autofluorescence interference, low photodamage to biological samples and deep tissue penetration.…”
Section: Introductionmentioning
confidence: 99%
“…In biosensing, ratiometric sensors employing Förster resonance energy transfer (FRET) are particularly attractive, as they enable the quantitative sensing of metabolite dynamics. Recently, hybrid small molecule–protein sensors, known as chemigenetic biosensors or semisynthetic biosensors, have emerged by tethering organic dyes with a sensing protein. They combine the good photostability, spectral flexibility, and photophysical properties of organic fluorophores with the genetic targetability and exquisite molecular recognition of proteins. Chemigenetic sensors have been effectively utilized to monitor the dynamics of cellular analytes (Table S2). Among them, Snifit sensors have been developed for ratiometric sensing of metabolites, relying on distance changes between donor–acceptor fluorophores within FRET pairs. However, the development of ratiometric chemigenetic biosensors for metabolites is still difficult due to two challenges: (1) Inefficient protein labeling with synthetic dyes in live cells, especially with large dyes, to achieve the quantitative 1:1 donor–acceptor pair for ratiometric measurement and (2) limited design strategies to achieve large distance changes between donor–acceptor fluorophores for achieving sensing with a large response range.…”
Section: Introductionmentioning
confidence: 99%